From the EU's Constitutional Convention to the Intergovernmental Conference: The balance between constitutional principles and national preferences - Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2003)
The European Constitutional Convention has presented the product of its work. The 'Draft Treaty Establishing a Constitution for Europe' contains four parts: Part I with 59 'founding' articles on the definition and objectives of the Union, its competencies, institutions, procedures and finances, part II with 54 articles incorparating the Charter on Fundamental Rights, part III, whose 342 articles establish the concrete provisions on the EU's institutional and procedural framework with regard to its specific policy areas, and part IV with 10 concluding articles on the procedure for revising the Constitution. The Intergovernmental Conference thus enters the decisive phase of its work. By the time the final text for parts I and II was presented on June 20, 2003, a consensus on the central EU power issues was expected to have been found. The broader the consensus, the more unlikely it is that the Intergovernmental Conference (IGC) that follows will unravel the Convention's set of compromises.(SWP Comments / SWP)
Keywords: 320